Pakistan: Preliminary National Greenhouse Gas Inventory - BAHADAR KHAN; M ANWAR BAIG (Journal of Applied Sciences and Environmental Management, 2004)
This paper represents a summary of the Preliminary Inventory of Greenhouse gases of Pakistan during 1999?2000?study period. The gases covered in the inventory are the direct greenhouse gases (carbon dioxide, methane & nitrous oxide) and indirect greenhouse gases (carbon monoxide, oxides of nitrogen, non?methane volatile organic compounds, halocarbons and sulphur dioxide). GHGs producing sectors in the country are divided into five sectors i.e. Energy, Industrial processes, Agriculture, Land?use change and forestry and Waste (guided by Intergovernmental Panel on Climate Change). In each of above a series of emission sources were identified and emission from all these are reported. Two approaches were used (Reference approach and Source category approach) for GHGs estimation. Energy sector is at top, due to its highest share in the anthropogenic source of emission, with Carbon dioxide at biggest shared among the direct and indirect GHGs. A total 93257.39 Gig grams (Gg) of CO2 emitted after consuming 1472953.89 Tera Joules (TJ) fossil fuels by the 137.5 million people. From the past few years, economic graph showed batter results, which stated that lot of resource mobilization has happened over the years, especially in energy sector to meet the country commercial/ domestic demands (Economic Survey of Pakistan, 1999?2000). Lot of interest shows from few years to explore the domestic resources and reduces the country import bill, particularly incase of Coal & Natural gas. Consumption of these hydrocarbons prescribed a scenario of acceding trend in the GHGs emission graph in near future. Inventory also addresses Mitigating options to cut down emissions pace of GHGs, which are not only feasible for country local environment, but based on domestic technology too.